A COMPARATIVE STUDY BETWEEN EXTROVERTED AND INTROVERTED PERSONALITIES ON SPEAKING SKILL (A STUDY OF YEAR 11 STUDENTS) - Nurinayah Magfirah; Syarifuddin Dollah; Munir Munir (Universitas Negeri Makassar, 2022)
This study aimed to (1) find out whether there is any difference significantly between extrovert and introvert students in speaking skill, (2) to know who are better in speaking between extrovert and introvert students. This study was descriptive quantitative research. This study used the ex post facto design also known as causal comparative design. In the data collection, used two instruments, there were questionnaire and speaking test. The population of this study was 194 with the total sample was 28 students. The study used two instruments, the questionnaire designed by Eysenck Personality Inventory (EPI) and speaking test. The scoring using rubric designed from Heaton 1988. The result of the study showed that there are 6 students categorized as extrovert and 22 students as introvert. The result of the independent sample “t” test showed that the value of the significance was 0.91. 0.91> 0.05. It meant that there is statistically significant difference between extrovert group and introvert. The total mean of introvert students was higher than extrovert 72.45 > 58.83. It meant that the introvert students at SMAN 6 Gowa better in speaking skill than extrovert students.